Assessment of Potential Anticancer Activity of Brown Seaweed Compounds Using Zebrafish Phenotypic Assay - Rusdi, Nur 'Afina; Kue, Chin Siang; Yu, Ke Xin; Lau, Beng Fye; Chung, Lip Yong; Kiew, Lik Voon (SAGE Publications, 2019)
Despite the extensive work on anticancer drug discovery, the number of potent lead compounds that enter the preclinical and clinical trials thus far is still low due to the poor selectivity and understanding in pharmacodynamics. In view of the homology between zebrafish embryogenesis and carcinogenesis in human, zebrafish embryos can be used in the screening platform to elucidate the molecular targets of potential anticancer compounds. In the present study, the possible targets modulating the potential anticancer effects of selected brown seaweed-derived compounds (ie alginate, fucoidan, phloroglucinol, fucosterol, and fucoxanthin) were examined. Teratogenic effects induced by the compounds were observed after 72 hours post-fertilization. Fucoidan, phloroglucinol, and fucosterol were observed to significantly reduce the pigmentation of the zebrafish in a dose-dependent manner at low concentrations (fucoidan, <60 µg/mL; phloroglucinol, <10 µg/mL; fucosterol, <3 µg/mL). On the other hand, embryos treated with fucoxanthin at 200 µg/mL and 300 µg/mL exhibited either phenotypes of curved trunk or bent tail. Further validation work using dual antiplatelet therapy (DAPT) and dorsomorphin as positive controls suggest that fucoxanthin might target the Notch and bone morphogenetic protein (BMP) pathways, respectively. Findings from this exploratory study henceforth have demonstrated the utility of zebrafish embryo to accelerate the discovery of potential compounds for targeted anticancer therapy. © The Author(s) 2019